2004
DOI: 10.1159/000076771
|View full text |Cite
|
Sign up to set email alerts
|

Physical Function and Health Status among Seniors with and without a Fear of Falling

Abstract: Background: Fear of falling (FF) is pervasive among older people and is an independent risk factor for decreased mobility and loss of quality of life. Although it is a serious health concern, little is known about the severity of the physical and health-related deficits in high-functioning fearful seniors. Objective: This study examined the physical correlates of FF in community-dwelling seniors in relation to their non-fearful counterparts and also explored the relevance of recent fall history. Subjects: Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
91
3
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(115 citation statements)
references
References 32 publications
15
91
3
6
Order By: Relevance
“…This result is consistent with studies of non-disabled, community-dwelling older adults, which found that those with reduced balance confidence demonstrated decreased lower-extremity strength and walking speed. 55,56 Likewise, several other studies of older community-dwelling individuals reported an association between 6MWT and measures of physical performance, activities of daily living, or selfreported activity. 14,19,57 Savci et al reported that functional independence in carrying out activities of daily living (Barthel Index) explained 61% of the variance in 6MWT performance in a similar group (EDSS < 6.5) of individuals with MS. 24 While they did not include other measures of physical performance or balance in their regression modelling, adding baseline HR and FSS to their model explained 81% of the variance in 6MWT distance (6% explained by the FSS).…”
Section: Discussionmentioning
confidence: 94%
“…This result is consistent with studies of non-disabled, community-dwelling older adults, which found that those with reduced balance confidence demonstrated decreased lower-extremity strength and walking speed. 55,56 Likewise, several other studies of older community-dwelling individuals reported an association between 6MWT and measures of physical performance, activities of daily living, or selfreported activity. 14,19,57 Savci et al reported that functional independence in carrying out activities of daily living (Barthel Index) explained 61% of the variance in 6MWT performance in a similar group (EDSS < 6.5) of individuals with MS. 24 While they did not include other measures of physical performance or balance in their regression modelling, adding baseline HR and FSS to their model explained 81% of the variance in 6MWT distance (6% explained by the FSS).…”
Section: Discussionmentioning
confidence: 94%
“…With the increasing flow of people between different countries, it is critical for clinicians to overcome language barriers and provide the best care to all patients. In the area of balance confidence, many studies have shown that Caucasian people have problems with their balance confidence [17][18][19][20][21][22][23][24], but we have been unable to obtain valid information from the Chinese population in this area because of a lack of reliable translated tools. Thus, there is need for balance confidence tools to be translated into the Chinese language.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have found reduced gait speed [8][9][10], reduced step or stride length [9,11], increased step width and increased double support phase (DSP) [9] in those with FOF but similar changes are observed with increasing age [12,13], depression [14] and with a history of falls [15], all of which are also associated with FOF. Rochat et al [16] found similar gait changes between groups with no FOF, FOF alone and FOF with activity restriction but while the differences between the no FOF and FOF alone groups were fully explained by confounding variables, those with FOF and activity restriction had decreased gait performance and increased gait variability independent of health and functional status.…”
Section: Introductionmentioning
confidence: 91%